Quality Service of Agricultural Business Permit Process In One Stop Service The Ministry Agriculture - Bhakti Nur Avianto; Trisnawati Yunika (Journal Research of Social Science, Economics, and Management, 2023)
This study examines the quality service of business license process at the Ministry of Agriculture and explores aspects that hinder their service for agricultural business license process (PTSP) at the Ministry of Agriculture's. This research uses qualitative descriptive research methods with interviews and documentation studies are used to collect data. This study uses data analysis techniques consisting of data reduction, responsiveness, assurance, and empathy along with indicators. The results showed that the quality of service for the business license process at the Ministry of Agriculture still needs to be improved, especially in the aspects of process speed, information disclosure, and responsiveness of service officers. Especially related to (1) Implementation of application-based service quality that has not provided convenience for business actors and lack of comfortable and clean facilities. (2) Strengthen the service officer's role in responding to any complaint of the service not in accordance with the wishes of the community regarding the timing of completion. (3) There are still low number of reliable employees in serving and assisting business actors. (4) There is no certainty of timely services and fees charged as well as those known by MSME business actors. Therefore, the Ministry of Agriculture needs to improve the quality of services by improving processes, increasing transparency and responsiveness of officers, and adjusting service costs to the quality provided.